find the product (x+3)( x+3 ) using the identity (x+y)*2 = x*2+2xy+y*2.
please this is my humble request that if u will answer please send photo of that solution
Answers
Answered by
0
Step-by-step explanation:
(x+3)(x+3)
=(x+3)^2
=(x)^2+(3)^2+2×x×3
=x^2+9+6x
Answered by
0
Answer:
Answer: Hence proved
Step-by-step explanation:
(X+y)^3 = (x+y)(x+y)^2
Open brackets
(X+y)(x^2+2xy+y^2)
X^3 +2yx^2+xy^2 + y^3 + 2xy^2 + yx^2
X^3 + 3yx^2+3xy^2 + y^3
May be it's helpful for you
Similar questions
Social Sciences,
7 months ago
Political Science,
1 year ago
Math,
1 year ago
Biology,
1 year ago
Physics,
1 year ago